Inheritance of glyphosate resistance in Kochia scoparia - Niehues, Kindsey (Kansas State University, 2014)
Extensive, often exclusive, use of glyphosate in crop production has resulted in evolved glyphosate resistance in several weed species globally. Kochia is a competitive summer annual weed, well adapted to the North American Great Plains and has recently evolved resistance to glyphosate by gene amplification of 5-enolpyruvyl shikimate 3-phosphate synthase (EPSPS), the target-site of glyphosate. The overall objective of this research was to investigate the genetic basis of glyphosate resistance in kochia, specifically to study 1) the inheritance of glyphosate resistance and 2) determine the chromosomal distribution of EPSPS gene copies. Homozygous resistant (R) and susceptible (S) parental lines of kochia were identified. Using these parents, reciprocal crosses were performed to produce F₁ progeny. As expected for a nuclear encoded EPSPS gene, F₁ plants from both crosses survived various doses of glyphosate application. However, F1 plants showed intermediate shikimate accumulation and EPSPS gene copies (relative to ALS reference gene) compared to parents. F₂ progeny were produced by selfing F₁ plants. In response to 870 g ae ha⁻¹ glyphosate, F₂ plants (n=115) segregated into 3:1 (R:S) implying a Mendelian monogenic segregation of glyphosate resistance in kochia. Additionally, relative EPSPS gene copies ranged from 1-10 in the F₂ progeny (n=51) with a genotypic segregation of 40:11 (plants with 3 or more EPSPS gene copies: plants with 1 EPSPS gene copy). In F₂ dose-response, a correlation between the level of resistance and relative EPSPS gene copies was observed. Genomic organization of the amplified copies using fluorescent in situ hybridization (FISH) displayed a single and larger hybridization site of the EPSPS gene on one pair of homologous chromosomes in R compared to a faint hybridization site in S samples of kochia. These results suggest possibility of amplification of EPSPS gene mediated via unequal recombination leading to the evolution of the glyphosate resistance in kochia.
Keywords: Weeds; Kochia scoparia; Glyphosate; Agronomy (0285)